Change of Measure in Midcurve Pricing. Issue 106 (23rd March 2020) - Feldman, Konstantin
Abstract : We derive measure change formulae required to price midcurve swaptions in the forward swap annuity measure with stochastic annuities' ratios. We construct the corresponding linear and exponential terminal swap rate pricing models and show how they capture the midcurve swaption correlation skew.